The Effect of Preoperative Pelvic Floor Muscle Training on Incontinence Problems after Radical Prostatectomy: A Meta-Analysis - Rangganata, Ervandy; Rahardjo, Harrina Erlianti (Urology Journal, 2021)
Purpose: To evaluate whether additional PFMT, which began before radical prostatectomy and resumes immediately after catheter removal, will significantly improve urinary incontinence after RP. Materials and Methods: We reviewed articles obtained from MEDLINE, CENTRAL, EBSCOHost, CINAHL, and Elsevier from July – August 2020, which compared preoperative PFMT with postoperative PMFT or non-PFMT, with continence incidence parameters. There were no restrictions on the definition of incontinence, treatment regimens, and radical prostatectomy surgical approach. The risk of bias was assessed using the Cochrane Risk of Bias Assessment Tool. A meta-analysis was also carried out to pool the effect estimates. Results: We included 12 eligible studies in this review, 11 of which we included in the meta-analysis. The PFMT initiated preoperatively significantly reduced the incidence of persistent urinary incontinence at 1, 3, and 6 months postoperatively with an OR of 0.58 (95% CI, 0.41–0.81), 0.57 (95% CI, 0.43–0.74), and 0.38 (95% CI, 0.17-0.83). There was no difference in improvement in patients' incontinence at 12 months postoperatively [OR = 1.31 (95% CI, 0.65-2.63)]. Conclusion: PFMT initiated before radical prostatectomy significantly reduced the incidence of urinary incontinence in the first, third, and sixth months postoperatively. At 12 months postoperatively, additional preoperative PFMT did not cause a significant difference in urinary incontinence incidence.